Biogenic synthesis of Fe2O3/ZnO bimetallic nanoparticles using fusarium oxysporum extract: Characterisation, optimisation, antimicrobial activity and methyl blue removal - Sayed-Ahmed, Mohamed Z.; Elsayed, Ashraf; Taha, Mai M.; Thaibah, Hilal A.; Alfarhan, Moaddey; Soliman, Aly A. A.; El-Bahkiry, Hesham S.; Radwan, Reda M.; Ali, Elham M. (Edelweiss Applied Science and Technology, 2025)
The fungus Fusarium oxysporum extract was used to synthesize iron/zinc oxide (Fe2O3/ZnO) bimetallic nanoparticles (NPs). To maximize NP yield, a central composite design (CCD) with independent variables, including pH, metal concentration, shaking speed, and incubation duration, was adopted. The greatest yield of the NPs was 1.985 mM at a pH of 7, a metal concentration of 7 mM, an incubation period of 48 hours, and a shaking speed of 140 rpm. These NPs showed potential antimicrobial effectiveness against both gram-positive and gram-negative bacteria. Furthermore, the NPs’ activity, which eradicates methyl blue ions, was assessed. The impacts of independent variables (pH, adsorbent concentration, dye concentration, contact time, and shaking speed) were investigated on dye ion biosorption during CCD. The findings indicated that methyl blue concentration, pH, and shaking speed all affected the optimization process. The biosorption of methyl blue ions was modeled using the Langmuir and the Freundlich equilibrium models. The Langmuir model demonstrated a better fit to the experimental data than the Freundlich model. A pseudo-first-order model was used to simulate the methyl blue adsorption process. This study’s novel contribution demonstrates the feasibility and effectiveness of using biosynthesized Fe/Zn oxide NPs as adsorbing agents for removing the environmental pollutant methyl blue dye.